CHARLES TAYLOR’S CRITIQUE OF EPISTEMOLOGY - chris O Abakare (PREDESTINASI, 2021)
ABSTRACT Charles Taylor’s critique of epistemology calls into question the subject/object dichotomy, which is central to epistemology at least in its modern phase. The fact that modern philosophy, which emerged in the seventeenth century, was the result of a shift towards the primacy of epistemology from Metaphysics, which adds enormous significance to such a critique of modern epistemology. This work examines Charles Taylor’s critique of epistemology. Charles Taylor’s critique of epistemology can be rightly understood as an intervention in the critical debates of modern epistemology. Taylor’s works, however, cannot be characterized merely as a critique of modern epistemology. Rather, his positions are also a critique of present-day philosophical critiques to modern epistemology. Certainly, his is a thorough critique of modern epistemology, but major portions of his writings are preserved to show how most of the present-day critiques are either pointless or not clear. Most importantly, he tries to show us how the various critiques of epistemologies themselves are imprisoned in the Cartesian epistemological picture. That is, even the critiques of Cartesian epistemology employ or widely share the points/crucial assumptions of Cartesian epistemology. Following are the fundamental points of Cartesian epistemology which the critiques to share uncritically. KEYWORDS: Charles Taylor, Epistemology, Critique of epistemology, Foundationalism.